A2_5 Rotation Aviation - Farrow, James Anthony; Hue, Jeremy; Miller, Robert; Checklin, Chris (Physics Special Topics, 2014)
This paper investigates the feasibility of an aircraft flying using the Magnus efect by replacing its conventional wings with cylindrical wings that rotate. It is found that if the wings were to maintain roughly their current size, the minimum angular frequency required to create enough lift at take-off is 37.69 rad/s and at cruising speed is 8.58 rad/s.